Do princípio da legalidade à supremacia da constituição: uma resposta hermenêutica - Bona, Marianne da Silveira (Universidade do Vale do Rio dos Sinos, 2014)
The dissertation analyzes the importance of historical and transdisciplinary knowledge to the sedimentation of understanding and critical interpretation of law. The axiology and supremacy of Brazilian Constitution is the fundamental point to the development of knowledge and legal hermeneutics as an open system which radiates in all spheres of law, especially facing the dogma of the concreteness of law stated by the ideals of Legal Positivism. The principle of legality shall be construed in accordance with the direct and immediate effect of fundamental rights by changing the mode of governance managers in respect of the fundamental right to good administration, forcing them to make better decisions facing the Constitution analysis of circumstances and not just the law of the case, but also of temporality and historicity, revisiting pre-understandings in order to merge the sense of being in the world horizons. Facing the constitutionalization of Administrative Law occurred substantial changes in the basis of discipline. The phenomenological-hermeneutic method runs through all the research and points out the way to approach the subject, leaving the historical, comparative and critical-scientific descriptive methods, focused on the specific tract of issues faced in the chapters that follow. The study is characterized by bibliographic research from readings, record keeping, abstracts and clashes of ideas of national and foreign authors with interpretations and analysis about the subject and, at the end, solutions and proposals for the dialectic of the questions asked.
Keywords: Hermeneutics; Supremacy; Constitution; Administration; Legality; Hermenêutica; Supremacia; Constituição; Administração; Legalidade; ACCNPQ::Ciências Sociais Aplicadas::Direito